2013
DOI: 10.1186/1471-2105-14-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics and genome distribution of osmoprotectants in soybean: identifying important components to face abiotic stress

Abstract: BackgroundDespite the importance of osmoprotectants, no previous in silico evaluation of high throughput data is available for higher plants. The present approach aimed at the identification and annotation of osmoprotectant-related sequences applied to short transcripts from a soybean HT-SuperSAGE (High Throughput Super Serial Analysis of Gene Expression; 26-bp tags) database, and also its comparison with other transcriptomic and genomic data available from different sources.MethodsA curated set of osmoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Using a comparative approach, we observed a similar pattern of seed-related pathway expression under water deficit in desiccation-tolerant and -sensitive grasses. This is not totally surprising as some seed-dehydration-associated pathways have well-characterized overlap with drought responses such as accumulation of osmoprotectants, LEA proteins, and ROS scavengers (41)(42)(43). For example, 22 of the 57 LEA genes in Arabidopsis have drought-induced expression but only 10 LEA genes have overlapping expression in drying seeds (44).…”
Section: Discussionmentioning
confidence: 99%
“…Using a comparative approach, we observed a similar pattern of seed-related pathway expression under water deficit in desiccation-tolerant and -sensitive grasses. This is not totally surprising as some seed-dehydration-associated pathways have well-characterized overlap with drought responses such as accumulation of osmoprotectants, LEA proteins, and ROS scavengers (41)(42)(43). For example, 22 of the 57 LEA genes in Arabidopsis have drought-induced expression but only 10 LEA genes have overlapping expression in drying seeds (44).…”
Section: Discussionmentioning
confidence: 99%
“…These genes were involved in multi-component binding-proteindependent transport systems for glycine, betaine, and camitine, and accumulated to high levels in the cell in response to increased external osmolality (Huang et al 2010). Additionally, proline is essential for primary metabolism in salt stress and plays a molecular chaperone role in maintaining the pH of the cytosolic redox status of the cell (Kido et al 2013). Previous research has indicated that proABC genes are related to the accumulation of proline and enable bacteria to withstand high osmotic pressure (Mahan and Csonka 1983).…”
Section: Absorption or Synthesis Of Compatible Solutesmentioning
confidence: 99%
“…Osmoprotectants, otherwise known as compatible osmolytes are non-toxic in nature, which play an important role in raising osmotic potential of cells under salt stress. In legumes, expression of osmolyte like trehalose, a non-reducing disaccharide has been detected in soybean (Kido et al, 2013), M. truncatula and common bean (López et al, 2008). Overexpression of genes encoding for compatible osmolytes have conferred transgenics tolerance to osmotic stress.…”
Section: Osmolytesmentioning
confidence: 99%